ROOTING OF APICAL FIG CUTTINGS AND THEIR FIRST DEVELOPMENT AT FIELD CONDITIONS - PIO, Rafael; RAMOS, José Darlan; CHALFUN, Nilton Nagib Jorge; CHAGAS, Edvan Alves; DALASTRA, Idiana Marina; CAMPAGNOLO, Marcelo Ângelo; CHALFUN, Maykon Zucari Haddad (Scientia Agraria, 2008)
The present work was developed in the dependences of the Fruticulture Section of the Agrarian Center of Sciences, of the State University of the Paraná West (UNIOESTE), Marechal Cândido Rondon-PR, among September of 2006 to March of 2007, with the objective of evaluating the development of figs plants obtained from a rooting process of cuttings using sucrose diluted in solutions of IBA at nursery. Woody cuttings of the apical part of the branch were collected, standardized with 20 cm of length and immerged in solutions with or without sucrose at 2% diluted in IBA (100, 200, 300 mg L-1 and testimonial absentee at IBA), for 24 hours. The cuttings were transferred to recipients measuring 26 x 14 cm, filled with substrate composed by soil and it sand (2:1 v/v) and stayed at nursery conditions under irrigation and temperature control. After 60 days, the roots and aerial part were evaluated. Another part of the plants were transferred to the field in recipients constituted of rigid plastic with 5 L of capacity, filled with a substrate composed by soil and cow mature (3:1 v/v). After 120 days, it was verified that both the cuttings treated with sucrose and IBA or the stakes that were not treated had similar behaviors at the field and that the treatment with IBA only increased the rooting percentage.